Retração, fluência e propriedades mecânicas de concretos produzidos com nanotubos de carbono sintetizados diretamente sobre clínquer - Luísa Araújo Rodrigues (2023)
Concrete is a nanostructured three-phase composite. Processes that take place at the nanoscale directly interfere with its performance. Important research has been developed using nanotechnology in building materials. Carbon nanotubes (CNTs) are cylinders in shape formed by graphene sheets. They can be presented in one layer, the single-walled carbon nanotubes, or in superimposed layers, the multi-walled carbon nanotubes. CNTs have been applied to pastes, mortars, and concrete as a way to improve their performance. In this work, the behavior of concretes produced with CNTs synthesized directly on clinker was evaluated. For this study, CP V – ARI cement was used, which was partially replaced by nanostructured clinker containing 0.2% and 0.4% carbon nanotubes to the total mass of cementitous materials. The performance of these concretes was compared with a reference concrete, without nanotubes. The influence of the addition of CNTs on workability, autogenous shrinkage, creep, compressive strength, elastic modulus, splitting, and flexural tensile strength as well as in the stiffness damage test was evaluated. The analysis of the results of mechanical properties shows that the best performance was obtained in concretes containing 0.2% of NTC, despite not presenting significant gains. In the drying shrinkage and basic creep tests, the incorporation of NTCs proved to be promising resulting in values 9% and 14% lower at 90 days, respectively, for concretes with 0.4% of CNTs.